Calcium and heterometallic manganese–calcium complexes supported by tripodal pyridine-carboxylate ligands: structural, EPR and theoretical investigations1. Issue 28 (28th July 2015) - Gerey, Bertrand; Gennari, Marcello; Gouré, Eric; Pécaut, Jacques; Blackman, Allan; Pantazis, Dimitrios A.; Neese, Frank; Molton, Florian; Fortage, Jérôme; Duboc, Carole; Collomb, Marie-Noëlle
<x xml:space="preserve">Abstract</x> Rare examples of heteronuclear μ-carboxylato bridged Mn–Ca complexes are reported.